The Effectiveness of E-Catalog in Preventing Fictitious Procurement: A System Vulnerability and Legal Implications Analysis - Lila Tania (Transpublika Publisher, 2025)
The Indonesian government has increasingly relied on digital systems to promote transparency and accountability in public procurement, notably through the introduction of the e-Catalog platform. This digital catalog is designed to standardize purchasing processes, reduce corruption, and eliminate fictitious procurement practices that have historically plagued government spending. However, concerns remain regarding its actual effectiveness and resilience against misuse. This study investigates the effectiveness of Indonesia's e-Catalog system in curbing fictitious procurement practices within the government sector. Employing a juridical-empirical methodology, this article scrutinizes the structural, technical, and regulatory mechanisms underpinning the e-Catalog, identifies potential system vulnerabilities, and explores the legal ramifications of its misuse. The findings indicate that while the system has significantly enhanced transparency and efficiency in procurement processes, it remains susceptible to exploitation through weak verification procedures, user misconduct, and integration gaps. The study advocates for robust policy reforms, including reinforced digital authentication, cross-platform integration, and strengthened legal enforcement to close loopholes and uphold procurement integrity.